Two Odorant-Binding Proteins of the Dark Black Chafer (Holotrichia parallela) Display Preferential Binding to Biologically Active Host Plant Volatiles - Ju, Qian; Li, Xiao; Guo, Xiao-Qiang; Du, Long; Shi, Chen-Ren; Qu, Ming-Jing (Frontiers in Physiology, 2018)
The dark black chafer (DBC), Holotrichia parallela, is an important pest of multiple crops. Insect host-searching behaviors are regulated by host plant volatiles. Therefore, a better understanding of the mechanism linking the chemosensory system to plant volatiles at the molecular level will benefit DBC control strategies. Based on antenna transcriptome data, two highly expressed antenna-specific odorant-binding proteins (HparOBP20 and 49) were selected to identify novel DBC attractants using reverse chemical ecology methods. We expressed these proteins, mapped their binding specificity, and tested the activity of the plant volatiles in the field. The ligands used in the binding specificity assays included 31 host-plant-associated volatiles and two sex pheromone components. The results showed that (1) HparOBP20 and 49 are involved in odor recognition; (2) these proteins bind attractive plant volatiles strongly and can therefore be employed to develop environmentally friendly DBC management strategies; and (3) the green-leaf volatile (Z)-3-hexenyl acetate shows a high binding affinity to HparOBP20 (Ki = 18.51 μM) and HparOBP49 (Ki = 39.65 μM) and is highly attractive to DBC adults, especially females. In the field test, a (Z)-3-hexenyl acetate trap caught an average of 13 ± 1.202 females per day, which was significantly greater than the corresponding male catch (F2,6 = 74.18, P < 0.0001). (Z)-3-Hexenyl acetate may represent a useful supplement to the known sex pheromone for DBC attraction. In the present study, the binding characteristics of two HparOBPs with host plant volatiles were screened, providing behaviourally active compounds that might be useful for DBC control, based on reverse chemical ecology.